Le promeneur londonien au xixe siècle : une excursion dans l’obscur - Max Duperray (Cahiers Victoriens et Edouardiens)
This paper aims at analysing the appearance of a genre : urban wandering and its motives. The emergence of a witness sensitive to effects introduces the field of obscurity, a metaphor which underlies the discourse on poverty but also leads to a generic problem : what kind of text is produced by urban wandering ? The observer disrupts the picture. He is at the heart of a labyrinth and, in the wake of the Gothic tradition, his disorientation combines obscurity and unintelligibility. From Charles Lamb and De Quincey to Arthur Machen and even (a little later) Virginia Woolf, among others, the figure of the invisible bohemian recalls Baudelaire’s flâneur and the fictional character writing fiction. The city is « textualised » and the Peripatetic novelist torn between alienation and contamination becomes the origin of the Sublime, as signs prevail over their referent. The matrix for such texts is Poe’s « Man of the Crowd » with its opening on detection. The city becomes organic ; it turns into the fantastic body of paranoid fictions which amplify and express the poetics of urban peregrinations : an encounter of the Self and its Other.